Rapidly Solidified Powder Aluminum Alloys 1986
DOI: 10.1520/stp33035s
|View full text |Cite
|
Sign up to set email alerts
|

Powder Metallurgy Processing of Aluminum Alloy 7091

Abstract: Aluminum alloys produced by powder metallurgy (PM) processing have the potential to solve many material problems in aerospace systems. However, to optimize fully the performance of these materials, strict processing control is required. For example, the breakup and redistribution of oxides, which is key to achievement of maximum properties, is directly related to vacuum degassing, hot pressing, and subsequent working of the material. An analysis of each of these steps is reviewed for aluminum PM Alloy 7091 wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1987
1987
2010
2010

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…A regression line drawn through the data indicates an increasing tendency for reduction with increasing ampule pressure. Griffith, Kim, and Froes (42) have shown that aluminum hydroxide on the surface of aluminum powder decomposes, releasing water which reacts with aluminum to release hydrogen. Hydrogen will reduce U30S to form U409.…”
Section: Reaction Productsmentioning
confidence: 99%
“…A regression line drawn through the data indicates an increasing tendency for reduction with increasing ampule pressure. Griffith, Kim, and Froes (42) have shown that aluminum hydroxide on the surface of aluminum powder decomposes, releasing water which reacts with aluminum to release hydrogen. Hydrogen will reduce U30S to form U409.…”
Section: Reaction Productsmentioning
confidence: 99%